Assessment of maturity of mining industry simulation - Stothard, Phillip; Swadling, P. (AusIMM, 2010)
Mining is a mature user of high technology. However, the maturity of mining simulation use is unclear. This paper compares mining to other industries to assess maturity. Simulation technology has been implemented at varying levels of complexity, sophistication and success. Rapid advances in hardware and software make low cost, mass market and high end small market computer based simulations readily accessible. When mining is compared to other industries, simulation acceptance appears immature, particularly in the areas of risk and hazard reduction, simulation design, operational command and control and a formal implementation framework. The question asked by this paper is: 'What is the level of maturity of interactive computer based simulation in the mining industry when compared to other industries?' The paper reviews some of the many interactive visualisations and simulations developed for the mining industry. The outcome is a basic qualitative maturity model of simulation in the mining industry as of 2010.